O trabalho do professor de língua estrangeira representado e avaliado em diários de aprendizagem - Mazzillo, Tania Maria da Frota Mattos (2006)
The present work is part of a research project being developed by the Group ALTER-LAEL. The Group ALTER-LAEL is a research group concerned with questions related with human action and texts produced in or about the educational work situation. Thus, the group s main research project focuses on the development of more solid knowledge on how texts, social activities and actions are inter-related. This research, therefore, focuses on the characterization of texts in which external agents interpret and evaluate the actions performed by workers in their jobs (texts of work interpretation). More specifically, this research aims at identifying linguisticdiscursive characteristics of the interpretation and evaluation of teachers´ classroom actions, as registered in learners diaries, as well as it aims at identifying from which perspectives such actions are evaluated. Broadly speaking, learners diaries are diaries written by researchers engaged in learning situations, who wish to register their progress in language learning. The data used in this research comes from the diaries of two distinct researchers who attended German and Spanish lessons, aiming at a better understanding of the language learning process. In order to develop this research, we adopted the views of the Interacionismo Sociodiscursivo, which develops a theory based on the sociocultural theory of development and which considers language to have a fundamental role in human development. We have also adopted the views of French Ergonomics (Saujat, 2002 and 2004; Amigues 2002, 2003 e 2004) and of the Activity Clinic (Clot, 1999 and Clot and Faïta, 2000) disciplines which study situated work activity, in the light of the same sociocultural theory, thus being compatible with the former theory. For the analysis of the different voices or perspectives from which the actions are evaluated, the views of Authier-Revuz (1982, 1998/02 e 2000) were also adopted. Results show that language teachers´ work is represented as an interactive, instrumental and mental activity, which involves motive, intention and capacity. Results also show that human action is always subjected to interpretation and evaluation, and that evaluation is made from different ´perspectives´, or points of view, represented by different voices . Moreover, such evaluations refer not to isolated actions but to a sequence of actions (verbal and non-verbal) performed in order to implement a certain teaching task, such as the teaching of reading. The teachers´ motive, intention and capacity are also evaluated. Thus, we can say, that it is the teachers´ way of doing (or overall conduct) which is evaluated, or, in other words, the teachers´ professional style. Therefore, we conclude that the professional genres (or activity genres), a concept developed by Clot (99) and Clot and Faïta (2000) to explain individuals´ behavior at work, besides functioning as models for acting (cf. Bronckart, 2004), are also instruments for acting and criteria by which human action is evaluated